Exploring barriers to guideline implementation for prescription of surgical antibiotic prophylaxis in Nigeria. Issue 2 (19th April 2022) - Wood, Caroline E.; Luedtke, Susanne; Musah, Anwar; Bammeke, Funmi; Mutiu, Bamidele; Ojewola, Rufus; Bankole, Olufemi; Ademuyiwa, Adesoji Oludotun; Ekumankama, Chibuzo Barbara; Ogunsola, Folasade; Okonji, Patrick; Kpokiri, Eneyi E.; et al.
Abstract: Background: In Nigeria, the prescription of surgical antibiotic prophylaxis for prevention of surgical site infection tends to be driven by local policy rather than by published guidelines (e.g. WHO and Sanford). Objectives: To triangulate three datasets and understand key barriers to implementation using a behavioural science framework. Methods: Surgeons ( N = 94) from three teaching hospitals in Nigeria participated in an online survey and in focus group discussions about barriers to implementation. The theoretical domains framework (TDF) was used to structure question items and interview schedules. A subgroup ( N = 20) piloted a gamified decision support app over the course of 6 months and reported barriers at the point of care. Results: Knowledge of guidelines and intention to implement them in practice was high. Key barriers to implementation were related to environmental context and resources and concern over potential consequences of implementing recommendations within the Nigerian context applicable for similar settings in low-to-middle-income countries. Conclusions: The environmental context and limited resource setting of Nigerian hospitals currently presents a significant barrier to implementation of WHO and Sanford guidelines. Research and data collected from the local context must directly inform the writing of future international guidelines to increase rates of implementation.